Constraints in Adoption of Groundnut Cultivation Technology by the Farmers of Odisha (Indian Journal of Extension Education, 2020)
Groundnut is one of the important oilseeds and it contributes substantially to Indian economy. Its importance is notable in terms of nutrition as well as revenue generation. The present study was carried out in Dhenkanal and Angul districts of Odisha involving 220 respondents chosen through multistage simple random sampling procedure. Data were collected through pre-tested interview schedule. The constraints were measured at 3- point continuum i.e. not serious, serious and most serious with scores 1, 2 and 3 respectively. Institutional constraint was identified as the most serious among all the major dimensions of constraints. Inadequate knowledge on recommended practices of the production technology, paucity of credit facility, fluctuating market price, lack of awareness about new technology were the other constraints in decreasing order of seriousness. A well-orchestrated institutional mechanism need to be thought of for support and incentives to the farmers.